Photophysics applied to cavitands and capsules - Berryman, Orion B.; Dube, Henry; Rebek, Julius (Israel Journal of Chemistry, 2011)
The use of light as a stimulus to control functional materials or nano-devices is appealing, because it provides convenient control of triggering events where and when they are desired without introducing extra components to the system. Many photophysical and photochemical processes are extremely fast, giving rise to nearly instantaneous onset of events. However, these fast processes can be challenging to engineer into chemical systems. Supramolecular chemistry offers a convenient way to study and control photoprocesses. Given the reversible and self-programmed nature of modern host-guest systems, a modular approach can be considered in which different photoprocesses are coupled to obtain complex functions that emerge and are controlled solely by light inputs. In this review, we highlight recent examples of photoswitching and photophysics applied in the context of supramolecular host-guest systems, with a particular emphasis on resorcinarene-based cavitands and hydrogen-bonded capsules. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-04-02
Keywords: capsule; cavitands; encapsulation; photophysics; photoswitching